Historical and recent impacts on genetic structure of an island rabbit. Issue 8 (24th August 2018) - Ando, Haruko; Tsuda, Yoshiaki; Kaneko, Shingo; Kubo, Takahiro
ABSTRACT: Population fragmentation can reduce genetic diversity and increase the extinction risk of island endemic mammals, especially those with low dispersal ability. However, the intra‐island genetic structure and demographic history of mammals have not yet been well evaluated, especially on small geographic scales. We performed a genetic analysis of isolated island populations of the Amami rabbit ( Pentalagus furnessi ) on Tokunoshima Island using mitochondrial D‐loop region sequences and 8 nuclear microsatellite markers. Using data from fecal samples, we detected 2 genetic groups that corresponded with the northern and southern forested areas of the island based on the mitochondrial and nuclear genomes. We detected some admixture between the 2 groups in the nuclear genomes but did not detect gene flow between the 2 groups in the mitochondrial genomes. Although genetic diversity was higher in the southern population than in the northern population, the fixation index showed higher levels of inbreeding in the southern area with a signal of a recent bottleneck. We inferred the divergence time between the northern and southern groups (∼4, 320 years ago) using approximate Bayesian computations. These genetic structure patterns may have been generated by a combination of the demographic history of the species in relation to the geology of the island, human activities in the stone age, deforestation due to sugar plantations (beginning approximately 300 years ago), and recent human activities. This study highlights the importance of considering genetic structure in relation to complex factors within a single‐island habitat for appropriate genetic management of endemic mammals on islands. © 2018 The Wildlife Society. Abstract : Populations of an endemic rabbit were genetically differentiated at a small geographic scale within island habitat. This study highlights the importance of considering genetic structure in relation to complex factors within a single‐island habitat for appropriate genetic management of island endemic mammals.